Evaluating the use of robotic and virtual reality rehabilitation technologies to improve function in stroke survivors: A narrative review. (July 2019) - Clark, William E; Sivan, Manoj; O'Connor, Rory J
This review evaluates the effectiveness of robotic and virtual reality technologies used for neurological rehabilitation in stroke survivors. It examines each rehabilitation technology in turn before considering combinations of these technologies and the complexities of rehabilitation outcome assessment. There is high-quality evidence that upper-limb robotic rehabilitation technologies improve movement, strength and activities of daily living, whilst the evidence for robotic lower-limb rehabilitation is currently not as convincing. Virtual reality technologies also improve activities of daily living. Whilst the benefit of these technologies over dose-controlled conventional rehabilitation is likely to be small, there is a role for both technologies as part of a broader rehabilitation programme, where they may help to increase the intensity and amount of therapy delivered. Combining robotic and virtual reality technologies in a rehabilitation programme may further improve rehabilitation outcomes and we would advocate randomised controlled trials of these technologies in combination.